Addressing the Root of Political Corruption in Indonesia - Syarif, Laode Muhammad; Faisal, Faisal (Integritas : Jurnal Antikorupsi, 2019)
The root problem of political corruption in Indonesia is in fact on the governance of political parties. Political parties in Indonesia seem to be handicapped, and lose their ability in producing competent politicians. Political parties, too, seem to be weak in politic canalization, as they almost lose their role decencies to absorb, collect, and communicate political aspiration of the citizens in formulating and establishing public policies. It leads into a phenomenon where the citizens’ aspiration in accessing fair and just policies is blocked. Corrupt political system in Indonesia has an impact on the livelihoods of people. Corruption causes an increase in poverty, unemployment, employment in informal sectors, social gap, and complaint in public services. The statement is supported by a research-based article by Svetlana Absalyamova et al (2016) in Russia that found that there is a direct impact of corruption on social inequality. Consequently, there should be a systematic reform within the Indonesian political parties, especially in the area of political party financing, total abolition of oligarchs system to democratic/merit system, and serious effort in caderisation process.